PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SD NEGERI PEGAMBIRAN 1 - Fauziah, Gina; Hanikah; Hardiyanto, Novan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Picture and Picture cooperative learning model on IPAS cognitive learning outcomes and to describe the affective responses of fifth-grade students at SDN Pegambiran 1 on the history of the Indonesian nation's struggle. This study used a quantitative approach with a pre-experimental method (One-Group Pretest-Posttest Design). The research population consisted of 27 fifth-grade students at SDN Pegambiran 1, with a total sampling technique. Data collection techniques used 15 multiple-choice test items to measure cognitive learning outcomes and a 15-item questionnaire to measure affective responses. The results showed a significant increase in cognitive learning outcomes, where the average pretest score of 60.19 increased to 79.26 on the posttest, and classical completeness rose from 18.52% to 85.19%. Furthermore, the students' affective responses to the implementation of the Picture and Picture model obtained an average percentage of 81.02%, which falls under the "Very Positive" category across the dimensions of interest, attention, participation, and ease. Therefore, it can be concluded that the implementation of the Picture and Picture cooperative learning model has a positive and significant effect on IPAS learning outcomes and generates a highly positive affective response from fifth-grade students.